PENGARUH MEDIA KOMIK NGGAHI MBOJO (BAHASA BIMA) TERHADAP HASIL BELAJAR MATEMATIKA - Lala Intan Komalasari; Nur Islamiati; Hen Ardiansyah (STKIP Andi Matappa, 2021)
The purpose of this study was to find out the influence of Nggahi Mbojo Comic Media Influence (Bima Language) on The Learning Outcomes of Mathematics Students Class VI SDN 05 Hu'u. This type of research is experimental research. The research design used is Quasi-Experimental Design with the type of Pre-test and Post-test Design. Sampling in this study was carried out with purposive sampling techniques, obtained by the study population is a student of State Elementary School 05 Hu'u with a sample number of 42 students. Based on the results of the analysis of pretest data there was no significant difference between the control class and the experiment, which was 30.78 for the average experimental class and 31.96 for the control class. Nanum posttest data analysis results, the average posttest results of student learning results in the experimental class are superior to the control class, which is 84.03 in the control class and 91.32 in the experimental class. This shows that there is an influence on the use of comic learning media Nggahi Mbojo (Bahasa Bima) on the learning outcomes of students VI SDN 05 Hu'u.